The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/mec.14227
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt changes in the composition and function of fungal communities along an environmental gradient in the high Arctic

Abstract: Fungi play a key role in soil-plant interactions, nutrient cycling and carbon flow and are essential for the functioning of arctic terrestrial ecosystems. Some studies have shown that the composition of fungal communities is highly sensitive to variations in environmental conditions, but little is known about how the conditions control the role of fungal communities (i.e., their ecosystem function). We used DNA metabarcoding to compare taxonomic and functional composition of fungal communities along a gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 84 publications
(154 reference statements)
4
27
0
Order By: Relevance
“…4a). Saprophytic microbes have a wide range of functional abilities, and most soils contain most functional guilds of saprophytes (H€ attenschwiler et al 2005, Grau et al 2017, Semchenko et al 2018). The positive relationship, thus, supports the idea of a functional relationship between plants and microbes at the global scale Jackson 2006, Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…4a). Saprophytic microbes have a wide range of functional abilities, and most soils contain most functional guilds of saprophytes (H€ attenschwiler et al 2005, Grau et al 2017, Semchenko et al 2018). The positive relationship, thus, supports the idea of a functional relationship between plants and microbes at the global scale Jackson 2006, Chen et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fungal communities are well known to differ among habitats and to be patchily distributed (e.g. Grau et al ., ; Maghnia et al ., ; Chaudhary et al ., ), but OMFs have received little attention. Bunch et al .…”
Section: Orchid Mycorrhizal Fungus Identity and Orchid Distribution Amentioning
confidence: 97%
“…Fungal communities are well known to differ among habitats and to be patchily distributed (e.g. Grau et al, 2017;Maghnia et al, 2017;Chaudhary et al, 2018), but OMFs have received little attention. Bunch et al (2013) found that Cypripedium acaule associated with different OMFs in locations with different soil chemistry.…”
Section: Reviewmentioning
confidence: 99%
“…The earlier-mentioned global prevalence of spatial heterogeneity in soil microbial communities has potential implications for the interactions, survival, and evolution of virtually all terrestrial organisms. Both symbiotic mutualists and pathogens, two functional groups that have the most direct effects on plant and animal survival and reproduction, generally show strong compositional differences among habitats at a landscape scale (Geml et al, 2016;Grau et al, 2017). Because many of these exhibit substantial differences in interacting with various plants and animals, these soil microbes can enable the co-existence of closely related species, either by niche divergence, as shown in Osborne et al, or by density-dependent interactions.…”
Section: The Importance Of Preserving Habitat Diversity For the Consementioning
confidence: 99%